Sanksi Pidana Terhadap Suami Dalam Memperlakukan Isteri Saat Nusyuz - Ahmad Hafid Safrudin (Lembaga Penelitian, Penerbitan dan Pengabdian kepada Masyarakat (LP3M) IAIFA Kediri, 2020)
In this study, it can be seen that in the struggle of classical fiqh discourse, it turns out that the provision of restrictions on the rights and authority of the husband in treating nusyuz wives has been mentioned but is not clear and systematic. This is because in every discussion of the issue of nusyuznya the wife often forgets the basic principles or principles as parameters in giving limits on the rights and authority of the husband over the wife. Such as the principle of the pattern of husband-wife relations in Islam, the purpose of sanctioning and also looking at the legal substance of the nusyuz act itself, both in terms of quality, quantity and the things that trigger the emergence of the problem. In the context of Indonesia, where the majority of the population is Muslim and the family law they use is also Islamic law and the thick patriakhis culture, the issue of nusyuz law often harms the position of women, and can even be one of the triggers for acts of violence against them. Therefore, legal protection efforts such as criminal law can be used as a 'shield' in overcoming all forms of threats and acts of violence against them.